(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Binge-watching, the practice of watching multiple episodes of a television series in one sitting, has become increasingly common among young adults and may adversely affect executive functions such as attention, planning, self-regulation, and decision-making. This study assessed the association between binge-watching addiction and executive functioning among college students. Materials and Methods: A cross-sectional observational study was conducted among 265 college students aged 17–22 years in Srikakulam after Institutional Human Ethics Committee approval. Data were collected using a structured questionnaire and analyzed using SPSS with descriptive and inferential statistics. Results: The mean (SD) age was 20 (2) years, and 59.2% were females. Overall, 15.5% exhibited moderate problematic binge-watching, while 27.9% demonstrated relative weakness in executive functioning. Watching more than three consecutive episodes was significantly associated with problematic binge-watching (p < 0.05). A significant negative correlation was observed between binge-watching and executive functioning, indicating that higher binge-watching behaviour was associated with poorer executive skills. Conclusion: Demographic factors were not significantly associated with binge-watching behaviour. However, watching more than three consecutive episodes was a significant predictor of problematic binge-watching, which was associated with weaker executive functioning, particularly in emotional and behavioural regulation. These findings emphasise the need for interventions promoting healthy viewing habits among college students.